2018
DOI: 10.21873/cgp.20097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Vesicular Monoamine Transporter Gene Solute Carrier Family 18 Member 1 (SLC18A1) in Lung Cancer

Abstract: Most never-smokers with lung cancer do not respond to immune checkpoint inhibitors (ICIs). But for unknown reasons, a small proportion do show clinical benefit from the ICI pembrolizumab. Because of the good response of this group, it may be worthwhile assessing their SLC18A1 expression pre-treatment as a marker for potential clinical benefit. If SLC18A1 expression is low, a never-smoker may respond well to ICIs. High levels of expression would indicate a C5 tumor less likely to respond to ICIs. SLC18A1 might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Specifically, the high expression of the MEIS family is associated with the upregulation of C5. Previous studies by Lehrer et al have reported that high levels of C5 (immune silencing) will weaken the efficacy of immune checkpoint inhibitors (27). It is suggested that for patients with advanced cancer, interfering with the expression of MEIS while using immune checkpoint inhibitors may benefit the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the high expression of the MEIS family is associated with the upregulation of C5. Previous studies by Lehrer et al have reported that high levels of C5 (immune silencing) will weaken the efficacy of immune checkpoint inhibitors (27). It is suggested that for patients with advanced cancer, interfering with the expression of MEIS while using immune checkpoint inhibitors may benefit the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, C5 is positively correlated to MEIS1. A high level of C5 can impair the curative effect of immune checkpoint inhibitors, as reported by Lehrer and his colleagues [ 42 ]. Our findings showed that MEIS1 expression was strongly related to most immune cells in various types of cancer.…”
Section: Discussionmentioning
confidence: 91%
“…In cancer, dysregulation of SLC proteins has been shown to be oncogenic ( Xie et al, 2011 ; Mohelnikova-Duchonova et al, 2013 ; Bhutia et al, 2016 ; Sutherland et al, 2020 ). Many SLCs have been reported to be aberrantly expressed in LUAD and might serve as prognostic biomarkers ( Ikeda et al, 2015 ; Lehrer and Rheinstein, 2018 ). For example, elevated expression of SLC2A1 was associated with a poorer prognosis in LUAD patients ( Guo et al, 2020 ), while increased SLC18A1 expression was associated with significantly increased survival in LUAD patients ( Lehrer and Rheinstein, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many SLCs have been reported to be aberrantly expressed in LUAD and might serve as prognostic biomarkers ( Ikeda et al, 2015 ; Lehrer and Rheinstein, 2018 ). For example, elevated expression of SLC2A1 was associated with a poorer prognosis in LUAD patients ( Guo et al, 2020 ), while increased SLC18A1 expression was associated with significantly increased survival in LUAD patients ( Lehrer and Rheinstein, 2018 ). Additionally, aberrant SLC expression contributes to accelerated cell proliferation and invasion through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%